Altered brain dynamics of facial emotion processing in schizophrenia: a combined EEG/fMRI study - Philippa Hüpen; Barbara Schulte Holthausen; Christina Regenbogen; Thilo Kellermann; Han-Gue Jo; Ute Habel (Schizophrenia)
Abstract Facial stimuli are relevant social cues for humans and essential signals for adequate social interaction. Impairments in face processing are well-documented in schizophrenia and linked to symptomatology, yet the underlying neural dynamics remain unclear. Here, we investigated the processing and underlying neural temporal dynamics of task-irrelevant emotional face stimuli using combined EEG/fMRI in 14 individuals with schizophrenia and 14 matched healthy controls. Specifically, fMRI-informed region-of-interests were subjected to EEG-Dynamic Causal Modeling (DCM) analyses. Among six fMRI-informed EEG-DCM models, alterations in effective connectivity emerged between the primary visual cortex (V1) and the left occipital fusiform gyrus (lOFG). Specifically, individuals with schizophrenia showed enhanced backward connectivity from the lOFG to V1 for stimuli preceded by fearful (but not happy or neutral) faces. Connectivity strength was strongly correlated with self-reported difficulties in comprehending, processing, or articulating emotions (as assessed by the Toronto Alexithymia Scale-20) in individuals with schizophrenia but not in healthy controls. Enhanced backward connectivity from the lOFG to V1 potentially indicates heightened attention towards fearful surroundings and a propensity to assign salience to these stimuli in individuals with schizophrenia. The link to TAS-20 scores indicates that this neural deficit has real-world implications for how individuals with schizophrenia perceive and relate to their emotions and the external world, potentially contributing to the social and cognitive difficulties observed in the disorder.